Road traffic noise and cardiovascular disease risk factors in UK Biobank - Kupcikova, Z; Fecht, D; Ramakrishnan, R; Clark, C; Cai, Y (Oxford University Press, 2021)
Aims The aim of this study was to investigate the cross-sectional associations of modelled residential road traffic noise with cardiovascular disease risk factors [systolic (SBP) and diastolic blood pressure (DBP), C-reactive protein, triglycerides, glycated haemoglobin, and self-reported hypertension] in UK Biobank.